Structure and Reversibility of 2-dimensional Hexagonal Cellular Automata - Akin, Hasan; Siap, Irfan; Uguz, Selman (AMER INST PHYSICS, 2010)
2-dimensional finite cellular automata defined by local rule based on hexagonal cell structure are studied. Rule matrix of the hexagonal finite cellular automaton is obtained. The rank of rule matrices related to hexagonal finite cellular automata via an algorithm is computed. By using the matrix algebra it is shown that the hexagonal finite cellular automata are reversible, if the number of columns is even and the hexagonal finite cellular automata are not reversible, if the number of the columns is odd.
Keywords: Computer Science; Physics